Let, solution is
"y=\\sum_{n=0}^{\\infty}a_nx^n"Thus,
"y'=\\sum_{n=1}^{\\infty}a_nx^{n-1}"Hence, on simplification the differential equation
"y'=y+x"We get,
"a_0=a_1,a_2=\\frac{a_0+1}{2}, a_3=\\frac{a_0+1}{6}"and
"\\frac{a_n}{a_{n-1}}=\\frac{1}{n}, \\forall n\\geq 3"Thus,
"a_n=\\frac{6}{n!}, \\forall n\\geq 3"Hence, solution will be,
"y=a_0+a_1x+(\\frac{a_0+1}{2})x^2+(a_0+1)\\sum_{n=3}^{\\infty}\\frac{1}{n!}\\\\\n\\implies y=a_0+a_1x+(\\frac{a_0+1}{2})x^2+(a_0+1)(e^x-1-x-\\frac{1}{2}x^2)\\\\\ny=(a_0+1)e^x-x-1"
Comments
Leave a comment